2015
DOI: 10.1097/md.0000000000000483
|View full text |Cite
|
Sign up to set email alerts
|

Is Long-term Use of Benzodiazepine a Risk for Cancer?

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…In attempts to get a clear answer to this quandary, Kim et al published a 2016 meta-analysis of 22 observational studies (18 case–control and 4 cohort) which concluded an overall estimate of 19% increased cancer risk, with a significant dose-response trend, among benzodiazepine users over non-users [ 140 ]. There does exist a fine degree of granularity when it comes to the determination of cancer risk from benzodiazepines/Z-drugs as certain types of cancer (i.e., esophageal, brain, pancreatic) and certain agents (lorazepam, clonazepam, zopiclone) carry greater statistical weight, driving the overall association [ 137 , 140 ]. Given that most of the studies included in the meta-analysis are retrospective, the authors address the limitations fairly by reminding us of confounding by indication (cancer patients more likely to use anxiolytic medication) and unmeasured confounding (alcohol and smoking) [ 140 ].…”
Section: Cancermentioning
confidence: 99%
“…In attempts to get a clear answer to this quandary, Kim et al published a 2016 meta-analysis of 22 observational studies (18 case–control and 4 cohort) which concluded an overall estimate of 19% increased cancer risk, with a significant dose-response trend, among benzodiazepine users over non-users [ 140 ]. There does exist a fine degree of granularity when it comes to the determination of cancer risk from benzodiazepines/Z-drugs as certain types of cancer (i.e., esophageal, brain, pancreatic) and certain agents (lorazepam, clonazepam, zopiclone) carry greater statistical weight, driving the overall association [ 137 , 140 ]. Given that most of the studies included in the meta-analysis are retrospective, the authors address the limitations fairly by reminding us of confounding by indication (cancer patients more likely to use anxiolytic medication) and unmeasured confounding (alcohol and smoking) [ 140 ].…”
Section: Cancermentioning
confidence: 99%
“…The National Health Insurance is a single-payer system that was created by integrating 13 public insurance systems in 1995 to serve all residents of Taiwan. Approximately 99% of the estimated population of 23.7 million residents of Taiwan has been covered by this health-care insurance program since 1999 (12). The Taiwan Department of Health has authorized the National Health Research Institute (NHRI) to manage the claims data of the National Health Insurance Research Database (NHIRD).…”
Section: Methodsmentioning
confidence: 99%
“…Among these, 21 articles were excluded because of the following reasons: not relevant to our analysis (n 5 7), insufficient data (n 5 3), using psychotropic medication other than benzodiazepine (n 5 6), data from pre-existing cancer (n 5 3), using cancer mortality as a result, and using an acute biomarker as exposure. The remaining 21 studies including eighteen casecontrol studies 6,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and four cohort studies 8,9,28,29 were included in the final analysis (the study by Kaufman et al 13 was considered as two separate case-control studies). All of the included articles were written in English.…”
Section: Identification Of Relevant Studiesmentioning
confidence: 99%
“…Eight studies 6,7,13,23,[26][27][28] investigated breast cancer, three studies involved ovarian cancer, 14,19,21 two studies looked into colon cancer, 16,18 and five studies involved all types of cancer. 8,[26][27][28][29] They were conducted in the following countries: US (n 5 12), 6,7,[13][14][15]18,19,[21][22][23][24][25] Canada (n 5 2), 13,23 Sweden (n 5 3), 16,17,20 Denmark (n 5 1), 26 France (n 5 1), 29 and Taiwan (n 5 3). 9,27,28 Among 18 case-control studies, 13 studies 7,13,14,17,18,[20][21][22][23][24][25][26][27] were population-based studies, and five studies …”
Section: Characteristics Of Studies Included In the Final Analysismentioning
confidence: 99%